Model of Internalization of Akhlakul Karimah Values through Habituation of Islamic Manners in Early Childhood Education - Firdaus, Taufan; Sitika, Achmad Junaedi; Rukajat, Ajat (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Early childhood education plays a strategic role in shaping the foundation of character and Islamic morals from an early age, especially amid the challenges of moral degradation and the tendency for learning to be solely cognitive-oriented. Therefore, a character education model that emphasizes the contextual and continuous habituation of spiritual values is needed. This study aims to identify and analyze models of internalizing akhlaq al-karimah values through the habit formation of Islamic manners in early childhood. This study uses a qualitative approach with a case study method, through observation, in-depth interviews, and documentation techniques. The data were analyzed using data reduction, data presentation, and interactive conclusion drawing techniques. The results showed that the process of internalizing values was carried out through the habit formation of daily activities integrated with teacher role modeling, value reflection, and a religious and conducive learning environment. This pattern of habit formation is effective in fostering discipline, politeness, empathy, and responsibility in children. The resulting conceptual model consists of three main components, namely input in the form of the values of faith, honesty, responsibility, empathy, and cleanliness; process in the form of habit formation of Islamic manners through role modeling and value reflection; and output in the form of the formation of children's character with Islamic morals. This study confirms that systematic habituation of Islamic manners based on spiritual values is an effective strategy in Islamic character education for early childhood.